The feasibility of online dispute resolution in the Islamic banking industry in Malaysia: an empirical legal analysis - Oseni, Umar Aimhanosi; Adewale, Abideen Adeyemi; Omoola, Sodiq Olalekan (Emerald Group Publishing Ltd., 2018)
Purpose: The paper aims to examine the perceptions of three major stakeholders – bankers, lawyers and customers – in the Islamic banking industry in Malaysia to assess their behavioural intention to use the proposed online dispute resolution (ODR) mechanism. Design/methodology/approach: The study modifies the unified theory of acceptance and use of technology (UTAUT) within the context of ODR and its feasibility in the Malaysian Islamic banking industry. The model was extended to include trust in technology and trust in bank, which might have significant influences on the intentions of major stakeholders to use ODR for banking-related disputes. Actual use of the ODR was not included in the model as specified in the original UTAUT. Based on an internet survey, responses were obtained from about 109 respondents. The data obtained were subjected to multivariate statistical analyses. Findings: Results obtained indicate that trust in technology and effort expectancy are the most influencing determinants of the behavioural intention to use ODR among stakeholders in the Islamic banking industry in Malaysia. However, performance expectancy and social influence did not produce significant effects on behavioural intention. Research limitations/implications: Applying ODR in the banking industry in Malaysia will contribute to sustainable banking businesses in major Islamic finance jurisdictions. Being the most advanced region in global Islamic banking business, Asia sets the pace through theoretical and empirical studies in exploring innovative ideals such as ODR to promote sustainable business that not only ensures proper customer relationship management but also promotes consume protection. Practical implications: Results obtained suggest that the increasing use of internet banking will make ODR the preferable mechanism for dispute resolution in small-scale disputes in retail banking. This will also require some form of predictability, enforceability and Shari‘ah compliance in the process of dispute resolution for the major stakeholders to have full confidence in the ODR mechanism. The recently introduced Financial Ombudsman Scheme in the Islamic Financial Services Act 2013 of Malaysia is expected to serve as a good legal basis for the ODR mechanism. Originality/value: This appears to be one of the earliest attempts to examine the application of ODR in resolving Islamic banking disputes with a detailed analysis on its legal basis and implication.